RESEARCH OF HCF/LCF COMBINED CYCLE FATIGUE EXPERIMENTAL TECHNIQUE FOR BLADE - YOU Yu; ZHANG Wei; WANG ChunSheng (Jixie qiangdu)
To verify the fatigue life under high-low cycle combined loads of the blade the combined fatigue experimental technique was established. The orthogonal loads decoupling method was proposed based on the cylindrical rolled bearing and linear slide rail,and the coordinated loading control technique of a combined loads was presented by means of an external signal trigger. Then,the fatigue experiment of a certain type of ducted tail rotor fan blade under centrifugal load/Low Cycle Fatigue（ LCF） and aerodynamic load/High Cycle Fatigue（ HCF） was developed. The control precision of complex loads is superior to than ±1%,and the coordinated loading time interval is less than 0. 3 second. The experimental result indicates that the high-low cycle combined fatigue experimental technique can solve the technical problems of orthogonal loads decoupling and coordinated loading control,which provides the technical foundation for improving the high-low cycle combined fatigue life prediction precision of the blade.